Fatigue life prediction of orthotropic steel deck strengthened with UHPC under stochastic traffic load - Deng, Ming; Yi, Ju (Frontiers in Materials, 2023)
In recent years, the ultra-high performance concrete (UHPC) has been increasingly used to strengthen orthotropic steel decks (OSD) to solve the cracking problems at fatigue-prone details and pavement damage. In this paper, the fatigue life of a cable-stayed OSD bridge under stochastic traffic loads is calculated before and after the OSD was strengthened with the UHPC layer. The traffic data of the real bridge for one week is first obtained based on the weigh-in-motion system. Then, a stochastic traffic load on the bridge is simulated for its service life by the Monte Carlo method. A fatigue life analysis framework, which includes the traffic load simulation, a refined finite element model, the S-N curve and MINER linear cumulative damage criterion, is proposed for fatigue life prediction of OSD. The predicting results show that the fatigue life of three structural details, including the scallop cutout, the rib-to-deck joints and the rib-to-diaphragm joints, is significantly increased after strengthening by UHPC. The fatigue life of the three structural details is increased from 15.87 years, 13.89 years and 32.26 years to more than 100 years, respectively, as compared with the original OSD structure.